Tribological Property of AlCoCrFeNi Coating Electrospark-Deposited on H13 Steel - Ke Lv; Guanglin Zhu; Jie Li; Xiong Cao; Haonan Song; Cean Guo (Metals)
AlCoCrFeNi coatings were electrospark-deposited (ESD) on H13 steel substrates, and their nano-mechanical and tribological properties under a load of 2 N, 4 N, 6 N, 8 N, and 10 N were investigated by utilizing a nanoindentation instrument and a reciprocating friction and wear tester, respectively. The morphologies, composition, and phase structure of the as-deposited and worn AlCoCrFeNi coating were characterized using SEM (Scanning electron Microscope), EDS (Energy dispersive spectrometer), and XRD (X-Ray Diffraction). The results showed that the as-deposited AlCoCrFeNi coating with a nanocrystalline microstructure mainly consists of a BCC and B2 phase structure, and a gradient transition of elements between the coating and the substrate ensures an excellent bond between the coating and the substrate. The hardness of the AlCoCrFeNi coating exhibits an 8% increase, while its elastic modulus is reduced by 16% compared to the H13 steel. The AlCoCrFeNi coating remarkably increased the tribological property of the H13 steel under various loads, and its wear mechanism belongs to micro-cutting abrasive wear whilst that of the H13 steel can be characterized as severe adhesive wear. The friction coefficient and weight loss of the AlCoCrFeNi coating decrease with increasing load, both following a linear relationship with respect to the applied load. As the load intensifies, the work hardening sensitivity and oxidation degree on the worn surface of the coating are significantly enhanced, which collectively contributes to the improved tribological performance of the AlCoCrFeNi coating.